BUKHORO MUSEUMIDAGI ERON TANGALARI - Шерали Гулямович Джураев (American Journals Publishing, 2025)
This article provides information about the collection of Iranian coins stored in the Bukhara Museum. The article highlights the history of the arrival of these exhibits in the museum and the description of numismatic materials.
Keywords: Bukhara Museum, Numismatics, exhibit, coin, fund